2012
DOI: 10.1021/mp200566k
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Charge Distribution on Self-Association and Viscosity Behavior of Monoclonal Antibody Solutions

Abstract: The present work investigates the influence of electrostatic surface potential distribution of monoclonal antibodies (MAbs) on intermolecular interactions and viscosity. Electrostatic models suggest MAb-1 has a less uniform surface charge distribution than MAb-2. The patches of positive and negative potential on MAb-1 are predicted to favor intermolecular attraction, even in the presence of a small net positive charge. Consistent with this expectation, MAb-1 exhibits a negative second virial coefficient (B₂₂),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
331
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 244 publications
(346 citation statements)
references
References 49 publications
15
331
0
Order By: Relevance
“…Increases in intermolecular associations between antibody molecules at high protein concentrations have been previously correlated to elevated solution viscosity values. 5,51 This effect can be attributed to the antibody network formation at high protein concentration, which affects the packing volume fraction of the antibody and ultimately results in an increase in solution viscosity. 10 For example, Pathak et al demonstrated that the presence of reversibly associated clusters at high protein concentrations contributed to an increase in solution viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in intermolecular associations between antibody molecules at high protein concentrations have been previously correlated to elevated solution viscosity values. 5,51 This effect can be attributed to the antibody network formation at high protein concentration, which affects the packing volume fraction of the antibody and ultimately results in an increase in solution viscosity. 10 For example, Pathak et al demonstrated that the presence of reversibly associated clusters at high protein concentrations contributed to an increase in solution viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…This network is hypothesized to consist of a transient formation of protein clusters whereby the interactions result in short lifetimes for rearrangement. In the case of MAb 1 and MAb 2, these interactions appeared to be dominated by electrostatics as suggested by the studies by Yadav et al (2012a). Molecular dynamics simulations can be useful in gaining additional insights into which specific regions of the MAbs are involved in network formation.…”
Section: Dilute Solution Static and Dynamic Light Scattering Measuremmentioning
confidence: 86%
“…The influence of surface charge distribution in governing the different high concentration solution behavior of MAbs 1 and 2 was assessed in recent work by studying the chargeswap mutants of MAb 1 and MAb 2 (Yadav et al 2011c(Yadav et al , 2012a. The details of these charge-swap mutants, including specific amino acid changes, are discussed in Yadav et al (2011c).…”
Section: Dilute Solution Static and Dynamic Light Scattering Measuremmentioning
confidence: 99%
See 2 more Smart Citations